2014
DOI: 10.1530/jme-14-0212
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals tissue-specific regulation of prolactin receptor gene expression

Abstract: Prolactin (PRL), acting via the PRL receptor (PRLR), controls hundreds of biological processes across a range of species. Endocrine PRL elicits well-documented effects on target tissues such as the mammary glands and reproductive organs in addition to coordinating wholebody homeostasis during states such as lactation or adaptive responses to the environment. While changes in PRLR expression likely facilitates these tissue-specific responses to circulating PRL, the mechanisms regulating this regulation in non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 57 publications
(86 reference statements)
1
27
0
Order By: Relevance
“…For example, in addition to the abundantly expressed and widely conserved exon 1 among different species, the PRLR gene has multiple additional first exons because of alternative splicing in different tissues (52). Different tissues can have different 5Ј-regions of the Prlr gene (53).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in addition to the abundantly expressed and widely conserved exon 1 among different species, the PRLR gene has multiple additional first exons because of alternative splicing in different tissues (52). Different tissues can have different 5Ј-regions of the Prlr gene (53).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…It remains to be determined whether Zfhx3 directly binds to Prlr promoter, and if so where it binds. Porcine Prlr promoter, which is the best studied so far among different species for the potential use of Prlr as a marker for reproductive performance (56 -59), has 12 alternative first exons (52). Similar to porcine Prlr, the 5Ј region of mouse Prlr is also quite large, spanning more than 120 kb (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Some reports revealed that it can play an antiapoptotic role and that it can stimulate angiogenesis, but other reports showed that IGFBP3 could inhibit angiogenesis and counteract the effect of VEGF. 27 Although an increased level of IGF1 in vitreous proliferative diabetic retinopathy is seen, the IGFBP1 and IGFBP3 levels were unchanged. 57 In turn, infants with ROP had a lower plasma IGFBP3 level.…”
Section: Discussionmentioning
confidence: 95%
“… 51 Some of these proteins can act through IGF-independent mechanisms. 27 Moreover, retinas in a hypoxia condition showed a decreased expression of IGFBP7 compared to retinas in a normal condition. 13 Lofqvist et al 59 detected a greater expression of IGF2 than IGF1 in the photoreceptors and blood vessels of mouse retina.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation